HISTORIOGRAPHY OF THE SOCIO-ECONOMIC SITUATION OF MADRASAHS OF THE BUKHARA EMIRATE - Imamov Ulug’bek Ismailovich (Journal Park Publishing, 2023)
The madrasah is a higher educational institution. Among the religious sciences, this is an educational building where education is given in mathematics, rhetoric and logic, linguistics, jurisprudence, philosophy, calligraphy, music, medicine, geography, astronomy and other sciences. The founders of the madrasah allocated special property - waqf - for the maintenance of the madrasah and appointed a trustee to manage this property. Part of the donations to the madrasah is directed to repair the building of the madrasah, a certain part is given to mutavvalis, mudarrises, students, imam of the mosque, muezzin, hairdresser, cleaner and other servants. In the late 19th and early 20th centuries, the curriculum of the Central Asian madrasas was somewhat reformed, and the subjects taught in them included Turkish, Russian, French, English, physics, agriculture, accounting, hygiene, psychology, methodology, trigonometry, political economy. and commerce began to come. The article presents the historiography of the socio-economic situation of the madrasah during the time of the Bukhara mangit-emirs.
Keywords: Madrasahs, a'la (higher), avsat (middle), adno (lower), certification (sanad), theology and jurisprudence, hadith studies and tafsir, salary, bekasampos, avshata tadrisi, asfol tadrisi, islamic and educational knowledge.